EFFECTIVENESS OF LEARNING TRAJECTORY BASED ON RME-ETHNOMATHEMATICS - Lely Kurnia; Eka Pasca Surya Bayu; Kurnia Rahmi Yuberta (Universitas Muhammadiyah Surabaya, 2024)
The results of the preliminary study show that the System of Linear Equations in Two Variables learning process in junior high schools tends to use direct mathematical models and presents material that is not related to daily life experiences, thereby decreasing students' motivation towards mathematics. This is the basis for designing learning trajectory in the form of activities based on students' experiences. This research is design research with the Plomp model. In the first phase, preliminary research was carried out consisting of needs analysis, curriculum analysis, concept analysis, characteristics analysis and literature review. In the second phase, the prototyping phase was carried out with a series of formative evaluations: self-evaluation, expert validation, one-to-one evaluation and small group. The trial was carried out at Al Islah private junior high school in Bukittinggi city. Based on the results of the implementation of RME-based etnomathematics learning design in class VIII SMP/MTs, it has effectively had an impact on learning outcomes. This result can be seen from the percentage of completeness obtained by students using student books with RME-based ethnomathematics where 86.7% of students were able to complete the post test at the field test stage.